Fire safety and protection measures in heritage buildings with special consideration on museum buildings in Malaysia - Salleh, Nurul Hamiruddin (2012)
Fire is one of the greatest threats to heritage buildings not only to the buildings’ occupants but also to the buildings’ fabrics and contents. Heritage buildings are irreplaceable, in addition to being vulnerable to fire due to several factors: large scale buildings, flammable priceless contents, and weak existing structures to fire resistance. Unfortunately, until today, there are no sufficient legislations or guidelines on fire safety for heritage buildings in Malaysia. This study audits the current fire safety measures and examines the management of fire safety in Malaysian heritage buildings that focuses on museum buildings. A combination of observations, interviews, questionnaires and case studies was employed to provide primary data in this study. Three museums were selected as case studies; each of them represented different criteria in order to gather various information and comparison as much as possible. Fire safety and protection measures in the studied buildings have been audited with reference to the requirements of the UBBL 1984, the Fire Services Act 1988, the Occupational Safety and Health Act 1994 and four relevant Malaysian Standards. The finding shows that there are several fire safety weaknesses in the heritage buildings that could put people and heritage properties on fire risks.